2005
DOI: 10.1116/1.1868652
|View full text |Cite
|
Sign up to set email alerts
|

Fermi level pinning on Si0.83Ge0.17 surface by inductively coupled plasma treatment

Abstract: Effects of inductively coupled plasma (ICP) treatment on Fermi level pinning on the surface of Si0.83Ge0.17 was studied by current–voltage and x-ray photoemission spectroscopy measurements. ICP treatment induced the growth of silicon oxide, suggesting that Si vacancies are generated under the oxide. From linear fitting of Schottky barrier heights with metal work functions, it was found that surface state density increased from 6.60×1012to1.13×1013∕cm2eV by the ICP treatment, leading to the pinning of surface F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…7h, which can significantly increase the surface state density of semiconductors by doping or introducing defects on their surface and lead to the increment of current density as a consequence. 19,31,32 Another study indicates that when the metal tip (Fe) slides on a smooth and rough silicon wafer, the rough interface will induce a higher leakage current and current density. This is attributed to the Fermi level pinning effect at the high surface state of the rough interface causing more charge carriers to bounce back.…”
Section: Semiconductorsmentioning
confidence: 99%
See 1 more Smart Citation
“…7h, which can significantly increase the surface state density of semiconductors by doping or introducing defects on their surface and lead to the increment of current density as a consequence. 19,31,32 Another study indicates that when the metal tip (Fe) slides on a smooth and rough silicon wafer, the rough interface will induce a higher leakage current and current density. This is attributed to the Fermi level pinning effect at the high surface state of the rough interface causing more charge carriers to bounce back.…”
Section: Semiconductorsmentioning
confidence: 99%
“…As the silicon samples are processed by inductively coupled plasma reactive ion etching (ICP-RIE), the density of states can be readily increased by doping or introducing defects on the semiconductor surfaces. 31,32 In addition, the triboelectric current characterized during the two semiconductor sliding process also increases with the load pressure. 19 All the above results indicate that the triboelectric current can be readily induced by the tribovoltaic effect in two steps.…”
Section: Microscopic Mechanisms Of Dc-tengs Based On the Tribovoltaic...mentioning
confidence: 99%
“…In order to study the effect of the surface state density of the contact surface on the triboelectric current, they increased the surface state density of the silicon wafer by inductively coupled plasma‐reactive ion etching (ICP‐RIE) treatment. [ 101,102 ] The results showed that after ICP‐RIE treatment, the triboelectric current between tip and Si sample was obviously increase. These results were consistent with those predicted by the tribovoltaic effect.…”
Section: Applications In the Direct Current Teng Of C‐afmmentioning
confidence: 99%